Urgensi Public Relation dalam Membangun Citra Yayasan Nurhayati Bersama pada Masyarakat Tembung - Azzani, Icha Fahira; Khatibah, Khatibah; Ritonga, Elfi Yanti (YASIN, 2023)
In general, this thesis research aims to find out about how the Nurhayati Bersama Foundation builds its image without the role of public relations. This study uses a type of qualitative research with a descriptive approach. The data sources used in this study are secondary data sources and primary data sources obtained from observations, interviews, and documentation which will later be compiled and described in manuscript form. The results showed that (1) the process of building the image of the Nurhayati Bersama Foundation was carried out in several ways, namely promotion through distributing brochures, parades, learning recreation, improving the quality of education, improving physical and non-physical conditions, and establishing friendship with the community. (2) The media used in building the image are social media such as Instagram and WhatsApp which are used to post activities from the Nurhayati Bersama Foundation in the form of videos or pictures, then through print media such as brochures and banners. However, the methods used to build the image of the Nurhayati Bersama Foundation to the people of Medan Tembung did not go well because they encountered several obstacles. (3) the obstacle for the Nurhayati Bersama Foundation in building its image in society is the absence of a public relations role that assists the Nurhayati Bersama Foundation in building its image in society and the location of the school which is in an alley.